2007
DOI: 10.1371/journal.pgen.0030054
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Light and Temperature in the Regulation of Circadian Gene Expression in Drosophila

Abstract: Circadian clocks are aligned to the environment via synchronizing signals, or Zeitgebers, such as daily light and temperature cycles, food availability, and social behavior. In this study, we found that genome-wide expression profiles from temperature-entrained flies show a dramatic difference in the presence or absence of a thermocycle. Whereas transcript levels appear to be modified broadly by changes in temperature, there is a specific set of temperature-entrained circadian mRNA profiles that continue to os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
174
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(196 citation statements)
references
References 60 publications
(91 reference statements)
19
174
2
1
Order By: Relevance
“…Analyses were conducted for w 1118 control flies as well as two experimental genotypes, Hsp90 e6D/08445 and y w; tim 01 ; ftim P -tim cDNA g ('Tim 4 0 ), for which we observed accelerated temperature re-entrainment in behavioural analyses as outlined below. Transcript profiling of adult Drosophila heads revealed wide-spread temperature-driven as well as temperatureentrained circadian responses [2]. Notably, a set of heat-induced transcripts associated with the HSF1/HSP90 pathway was found to cycle in both wild-type and arrhythmic tim 01 mutant heads.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses were conducted for w 1118 control flies as well as two experimental genotypes, Hsp90 e6D/08445 and y w; tim 01 ; ftim P -tim cDNA g ('Tim 4 0 ), for which we observed accelerated temperature re-entrainment in behavioural analyses as outlined below. Transcript profiling of adult Drosophila heads revealed wide-spread temperature-driven as well as temperatureentrained circadian responses [2]. Notably, a set of heat-induced transcripts associated with the HSF1/HSP90 pathway was found to cycle in both wild-type and arrhythmic tim 01 mutant heads.…”
Section: Resultsmentioning
confidence: 99%
“…3), Boothroyd et al (2007) demonstrated temperatureentrained mRNA rhythms of all clock gene transcripts that also oscillate in LD cycles (per,tim,Clk,vri,cry,and Pdp1). The discrepancy could be explained by the difference in the experimental design.…”
Section: Role Of Transcriptional and Posttranscriptional Mechanismsmentioning
confidence: 96%
“…1b) (Glaser and Stanewsky 2005). Moreover, in a microarray study of Drosophila genes expressed rhythmically in temperature cycles, Boothroyd et al (2007) discovered that in tim 01 flies, some of the crucial clock or clock-input genes (per, tim, Clk, and cry) are rhythmically expressed during a temperature cycle but not after release into constant conditions.…”
Section: Location Of Thermal Receptors/tissueautonomous Temperature Rmentioning
confidence: 99%
See 2 more Smart Citations